Recurrent Facial Focal Seizures With Chronic Striatopathy and Caudate Atrophy—A Double Whammy in an Elderly Woman With Diabetes Mellitus. (January 2022) - Chatterjee, Subhankar; Ghosh, Ritwik; Ojha, Umesh Kumar; Diksha; Biswas, Payel; Benito-León, Julián; Dubey, Souvik
Seizures and involuntary movements are relatively rare, but well-known neurological complications of non-ketotic hyperglycemia. While hemichorea-hemiballism secondary to diabetic striatopathy is increasingly being reported, unilateral caudate atrophy resulting from chronic vascular insufficiency/insult in a backdrop of poorly controlled diabetes mellitus is sparsely described in literature. We herein report a 75-year-old woman with poorly controlled diabetes mellitus who presented with concurrent epilepsia partialis continua involving left side of her face and hemichorea on the right side in the context of non-ketotic hyperglycemia. Neuroimaging revealed a space-occupying lesion suggestive of low-grade glioma in the right superior frontal cortex and left-sided caudate atrophy as well. Possibly, space-occupying lesion in motor cortex acted as an inciting factor for seizures and non-ketotic hyperglycemia further lowered the seizures threshold. On the other hand, atrophied left caudate had led to persistent choreiform movements secondary to chronic uncontrolled hyperglycemia. The simultaneous presence of acute and chronic neurological complications of diabetes mellitus makes this case unique. It also highlights the need for strict control of blood glucose and utility of appropriate neuroimaging to rapidly diagnose and prevent further complications.